Flexural Behavior of Rubberized Reinforced Concrete Beams - A. Al-Azzawi, Adel; Shakir, Dalia; Saad, Noora (International Journal of Engineering and Technology, 2018)
In Iraq, the use of rubber waste material in concrete is an interesting topic due to its availability in large volumes. Researches of applications of rubber waste in concrete have been increased since 2003. Many studies carried out to investigate the performance of concrete using different ratios of rubber as a replacement to fine or coarse aggregate. In this research, rubber wastes from scrapped tires have been added as fiber to concrete mix with presence of 0.5% superplasticizer. The flexural behavior of concrete beams, mechanical properties of concrete and workability of concrete mixes have been studied. Rubber fibers ranging from (2-4) mm were added in percentages of 0.5% and 1%) of the cement weight. The results have demonstrated that the addition of rubber material as fibers in natural aggregate concrete enhances its ductility, compressive strength and tensile strength compared to the normal concrete. The effect of rubber fiber content is found to be significant on the behavior of tested beams. If the fiber content increased from 0 to 0.5% the cracking load increased by 60 % and ultimate load increased by 21%. For rubberized concrete, if the fiber content increased from 0.5 to 1.0%, the cracking load decreased 7% and ultimate load increased by 4%. Â Â Â